Digital Literacy and Critical Thinking Skills of Students in the Era Industry 4.0 - Furbani, Widiastuti; Purnawanti, Felisia; Dewi, A Erni Ratna; Sari, Nila; Thoriq, Thoriq (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
Industry 4.0 has introduced new challenges in the field of education, where digital literacy and critical thinking skills have become increasingly essential for students in navigating the ever-evolving flow of digital information. This study aims to analyze the relationship between digital literacy and students' critical thinking skills at the secondary school level. Utilizing a correlational survey method, data were collected from 250 students and analyzed using Pearson correlation and simple linear regression tests. The results indicate a significant positive relationship between digital literacy and critical thinking skills (r = 0.652, p < 0.01). Furthermore, regression analysis shows that digital literacy contributes 42.6% to the enhancement of students' critical thinking skills. These findings affirm that improving digital literacy can support the development of critical thinking through technology-based learning and more adaptive pedagogical approaches. Therefore, integrating digital literacy into the educational curriculum is crucial to equip students with essential skills to face the challenges of the digital era.